Cavity enhanced spectroscopy for measurement of nitrogen oxides in the Anthropocene: results from the Seoul tower during MAPS 2015. (5th June 2017) - Brown, Steven S.; An, Hyunjin; Lee, Meehye; Park, Jeong-Hoo; Lee, Sang-Deok; Fibiger, Dorothy L.; McDuffie, Erin E.; Dubé, William P.; Wagner, Nicholas L.; Min, Kyung-Eun
Abstract : Cavity enhanced spectroscopy, CES, is a high sensitivity direct absorption method that has seen increasing utility in the last decade, a period also marked by increasing requirements for understanding human impacts on atmospheric composition. This paper describes the current NOAA six channel cavity ring-down spectrometer (CRDS, the most common form of CES) for measurement of nitrogen oxides and O3 . It further describes the results from measurements from a tower 300 m above the urban area of Seoul in late spring of 2015. The campaign demonstrates the performance of the CRDS instrument and provides new data on both photochemistry and nighttime chemistry in a major Asian megacity. The instrument provided accurate, high time resolution data for N2 O5, NO, NO2, NO y and O3, but suffered from large wall loss in the sampling of NO3, illustrating the requirement for calibration of the NO3 inlet transmission. Both the photochemistry and nighttime chemistry of nitrogen oxides and O3 were rapid in this megacity. Sustained average rates of O3 buildup of 10 ppbv h −1 during recurring morning and early afternoon sea breezes led to a 50 ppbv average daily O3 rise. Nitrate radical production rates, P (NO3 ), averaged 3–4 ppbv h −1 in late afternoon and early evening, much greater than contemporary data from Los Angeles, a comparable U. S. megacity. These P (NO3 ) were much smaller than historical data from Los Angeles, however. Nighttime data at 300 m above ground showed considerable variability in high time resolution nitrogen oxide and O3, likely resulting from sampling within gradients in the nighttime boundary layer structure. Apparent nighttime biogenic VOC oxidation rates of several ppbv h −1 were also likely influenced by vertical gradients. Finally, daytime N2 O5 mixing ratios of 3–35 pptv were associated with rapid daytime P (NO3 ) and agreed well with a photochemical steady state calculation.